REHABILITATION OF FORMER MINING LAND AT PT RAJA KUTAI MAKMUR, BADAK BARU VILLAGE, MUARA BADAK DISTRICT, KUTAI KARTANEGARA REGENCY - Hong Lawing, Yustina (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Post-mining land generally exhibits low nutrient levels, requiring soil enhancement via the use of chemical or organic amendments. The application of fertilizers and lime markedly affects soil conditions and can improve soil fertility. Soil fertility is essential as a substrate for plant growth to support reforestation or reclamation initiatives. After the planting medium is properly prepared, it can be inhabited with plant species appropriate for the site's conditions. This study's methodology involves assessing land conditions through the analysis of soil characteristics and the measurement of soil pH in the designated area. The study's results indicated that the soil texture in the research region is classified as sandy loam and loamy sand, with an average pH of 4.5. To enhance soil conditions, 100 grams of lime is necessary for each planting hole, totaling 625 trees. Therefore, 62.5 kg of dolomite lime per hectare is required for soil rehabilitation in the post-mining region.